Carbon nanomaterials dedicated to heating systems. Issue 3 (3rd August 2015) - Agata Skwarek, Dr; Wroblewski, Grzegorz; Kielbasinski, Konrad; Swatowska, Barbara; Jaglarz, Janusz; Marszalek, Konstanty; Stapinski, Tomasz; Jakubowska, Malgorzata
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The paper aims to present the research results related to transparent heating elements made from carbon nanomaterials. Heating elements were fabricated only with cost-effective techniques with the aim to be easily implemented in large area applications. Presented materials and methods are an interesting alternative to vacuum deposition of transparent resistive layers and etching of low-resistive patterns. Fabricated heating elements were designed to be used as de-icing structures in roof-top windows. Design/methodology/approach – The paper presents the research results related to transparent heating elements made from carbon nanomaterials. Heating elements were fabricated only with cost-effective techniques with the aim to be easily implemented in large area applications. Presented materials and methods are an interesting alternative to vacuum deposition of transparent resistive layers and etching of low-resistive patterns. Fabricated heating elements were designed to be used as de-icing structures in roof-top windows. Findings – The sheet resistance of obtained layers was between 9 and 11 kΩ/□; however, double-walled carbon nanotubes showed significantly higher optical transmission (around 70 per cent) than graphene nanoplatelets (around 55 per cent for visible and near infrared range). The amount of polymer resin had the influence on the paints stability, electrical properties and coatings adhesion. Originality/value – Results show a novel method of fabrication of a large area and transparent heating elements with tunable resistance done through the change of spray coating paint composition.